P474 Prevalence of fecal incontinence and clinical characteristics of IBD patients in remission and treated with biologics – experience from a tertiary referral center. (21st January 2022) - Jelakovic, M; Turk, N; Brinar, M; Barisic, A; Grgic, D; Cukovic-Cavka, S; Krznaric, Z
Abstract: Background: Fecal incontinence (FI) is a debilitating disorder highly prevalent in inflammatory bowel disease (IBD) patients with reports in literature ranging from 20–80%. There is limited data on FI prevalence in IBD patients who are in remission, treated with biologics and their clinical characteristics. Methods: In this cross-sectional observational study we have included IBD patients in remission, treated with biologics. Demographics and medical data were collected from electronic medical charts while patients were screened for FI using the St. Mark's incontinence score (SMIS). Significant FI was characterized as SMIS ³6. Descriptive statistical analysis was used. Results: We included 57 patients (24 female/33 male) in clinical remission treated with biologics, median age 41 years (18–70), 23 patients had ulcerative colitis (UC) and 34 had Crohn's disease (CD). Median disease duration was 8 years (1–31). Significant FI was identified in 41 patient (71.9%) out of which 87.8% were in biochemical and 34.1% in endoscopical remission. FI was more prevalent among CD patients (76.4%) compared to UC (65.2%), but the difference did not reach statistical significance. FI was not significantly correlated to gender, type or number of biologics but there was significant positive correlation with disease duration (r=0.3139; p<0.05), especially for patients with disease duration longer than 5 years who had significantly higher mean SMIS score (9.1±4.6 vs 5.2±2.6; t -2.86; p<0.05). Furthermore, patients older than 50 years of age also had significantly higher average SMIS scores compared to younger patients (10.6±4.6 vs 7.6±4.3; t -2.09;p<0.05) Conclusion: FI is highly prevalent in IBD patients treated with biologics, even in those who have reached endoscopical remission. Clinicians should be aware of this disorder and use available screening tools especially in older patients with longer disease duration in order to further improve quality of life of these patients.